Cognitive therapy as an early treatment for post‐traumatic stress disorder in children and adolescents: a randomized controlled trial addressing preliminary efficacy and mechanisms of action. (15th December 2016) - Meiser‐Stedman, Richard; Smith, Patrick; McKinnon, Anna; Dixon, Clare; Trickey, David; Ehlers, Anke; Clark, David M.; Boyle, Adrian; Watson, Peter; Goodyer, Ian; Dalgleish, Tim
Abstract : Background: Few efficacious early treatments for post‐traumatic stress disorder (PTSD) in children and adolescents exist. Previous trials have intervened within the first month post‐trauma and focused on secondary prevention of later post‐traumatic stress; however, considerable natural recovery may still occur up to 6‐months post‐trauma. No trials have addressed the early treatment of established PTSD (i.e. 2‐ to 6‐months post‐trauma). Methods: Twenty‐nine youth (8–17 years) with PTSD (according to age‐appropriate DSM‐IV or ICD‐10 diagnostic criteria) after a single‐event trauma in the previous 2–6 months were randomly allocated to Cognitive Therapy for PTSD (CT‐PTSD; n  = 14) or waiting list (WL; n  = 15) for 10 weeks. Results: Significantly more participants were free of PTSD after CT‐PTSD (71%) than WL (27%) at posttreatment (intent‐to‐treat, 95% CI for difference .04–.71). CT‐PTSD yielded greater improvement on child‐report questionnaire measures of PTSD, depression and anxiety; clinician‐rated functioning; and parent‐reported outcomes. Recovery after CT‐PTSD was maintained at 6‐ and 12‐month posttreatment. Beneficial effects of CT‐PTSD were mediated through changes in appraisals and safety‐seeking behaviours, as predicted by cognitive models of PTSD. CT‐PTSD was considered acceptable on the basis of low dropout and high treatment credibility and therapist alliance ratings. Conclusions: This trial provides preliminary support for the efficacy and acceptability of CT‐PTSD as an early treatment for PTSD in youth. Moreover, the trial did not support the extension of 'watchful waiting' into the 2‐ to 6‐month post‐trauma window, as significant improvements in the WL arm (particularly in terms of functioning and depression) were not observed. Replication in larger samples is needed, but attention to recruitment issues will be required.